Development of exergaming simulator for athletes' training and exercise testing - Nurkkala, V.-M.; Kalermo-Poranen, J.; Ohtonen, O.; Hakkarainen, A.; Linnamo, V. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Digitalization is reaching into nearly every aspect of life. New technologies and applications are introduced in an increasing speed. However, for example virtual environments have rarely been applied to athletes' training and exercise testing. In 2013-2014 we developed an exergaming simulator that connects cardio equipment with virtual environments, games, immersive view and advanced motion control. The aim of the development was to bring motivation and enjoyment into training but also provide new tools for athletes' training and exercise testing. Athene has been piloted for different purposes, including gym training, senior activation, rehabilitation and exercise testing. Athene was piloted in the Vuokatti Athletes Testing Center in June 2014 for athletes training and exercise testing.